Analog Programmable Circuit Implementation for Memristor - Tahir, Fadhil Rahma; Ramadhan, Saif Muneam (Iraqi Journal for Electrical and Electronic Engineering, 2018)
In this work, a new flux controlled memristor circuit is presented. It provides a tool to emulate the pinched hysteresis loop. When driven the memristor by a bipolar periodic signal, the memristor exhibits a “pinched hysteresis loop” in the voltage-current plane and starting from some critical frequency, the hysteresis lobe area decreases monotonically as the excitation frequency increases, the pinched hysteresis loop shrinks to a single-valued function when the frequency tends to infinity. The design model numerically simulated and the physical implementation is achieved by using a field programmable analog array (FPAA). The circuit can be modeled and implemented with a changeable nonlinear function blocks and fixed main system blocks. The simplicity of the specific design method makes this proposed model be a very engaging option for the design of the memristor .